Myocardial Expression of Heart-Type Fatty Acid Binding Protein (h-FABP) in Various Cardiac Stress Conditions in Rats - Choosit, Sawapat; Wattanapermpool, Jonggonnee; Bupha-Intr, Tepmanas (Asian Medical Journal and Alternative Medicine, 2021)
Objective: The heart-type fatty acid binding protein (h-FABP) has recently been studied as the specific biomarker of myocardial injury. The present study aimed to investigate the potential stress conditions that affect the expression of h-FABP in the rat heart. Methods: Immunoblot analysis was used to quantify the protein expression of h-FABP in the heart under various cardiac stress conditions, including the effect of an aerobic training program, deprivation of ovarian sex hormones, angiotensin II-induced hypertension, doxorubicininduced cardiotoxicity, and type II diabetes. Results: No significant change in h-FABP protein expression in the heart was found after a 9-week exercise training compared to sedentary controls. Lack of female sex hormones for 10 weeks also had no effect on h-FABP protein expression. In addition, there was no change in h-FABP expression due to either 4-week angiotensin II infusion or doxorubicin treatment compared to their vehicle controls. A significant increase in h-FABP was demonstrated in the heart of spontaneous diabetes Torii (SDT) rats compared to those without diabetes (P-value < 0.0001). There was a high correlation between degree of hyperglycemia and the myocardial expression of h-FABP protein (r2 = 0.9252, P-value = 0.0022). Conclusion: The findings suggest that the expression of h-FABP in the heart is primarily regulated by available sources of energy, while cardiac hypertrophy and myocardial damage do not particularly contribute to h-FABP expression.